Historical distribution of species of the genus Haematoxylum (Leguminosae) in the Yucatan Peninsula, Mexico, based on herbarium specimens - Plasencia Vázquez, Alexis Herminio; Villegas, Pascale; Ferrer Sánchez, Yarelys; Zamora Crescencio, Pedro (Instituto de Ecología, A.C., 2017)
Background and Aims: Haematoxylum is represented in the Yucatan Peninsula by two species. The best-known species is logwood (H. campechianum) and recently, in 2014, H. calakmulense was described. The objectives of this study were to determine and characterize the areas of historical presence of both species in the Yucatan Peninsula and within the current system of National Protected Natural Areas (ANPs).Methods: To obtain historical records of both species the main herbaria that owe specimens of both species were consulted: CICY, CIQR, ENCB, MEXU, UADY, UCAM and XAL. To characterize the areas where records were taken, variables like land use, elevation, climate, morpho-edaphology and potential and active morpho-ecological systems in the Yucatan Peninsula were used. For both species the number of records present within federal Protected Natural Areas was also calculated.Key results: Haematoxylum campechianum is present in more scattered locations throughout the Peninsula, while H. calakmulense is mostly seen towards the center of the Peninsula, towards the south, around and inside the Calakmul Biosphere Reserve and in the periphery of the Bala’an K’aax Wildlife Protected Area. For both species most of the records were from areas with a combination of Leptosol-Vertisol soils, in a warm and subhumid climate with a predominance of high and medium semi-evergreen forests. Most of the populations of the two species develop outside of the protected areas.Conclusions: There are many information gaps and unexplored areas for H. campechianum and H. calakmulense. It would be relevant to take these into account in future studies, which would help to complement existing information and would allow for accurately determining their conservation status.